Recurring peripheral ameloblastoma at mandibular premolar region: A case report - Mustafa, Nazih Shaban; Kashmola, Muhanad Ali Hamdon; Subramaniam, Pram Kumar; Abdul Qader, Omar Abdul Jabbar; Ahmad, Abdul Rahim (Ectodermal Dysplasia Group-Turkey, 2019)
Peripheral ameloblastoma is an extraosseus type, rare form of ameloblastoma that proliferates on the soft tissue of tooth bearing region. It is usually an exophytic odontogenic tumour that exhibits with either smooth or irregular surface and is mainly located in the mandibular region namely the gingival area. This lesion is mainly limited by the periosteum but a larger lesion can have features of bony marginal saucerization as well as displacement of teeth. We hereby report a case of recurring peripheral ameloblastoma on the mandibular left premolar region in a 37 year-old Malay gentleman seen at the Kulliyyah of Dentistry, International Islamic University Malaysia.